Do I Care if I Get Credit for My Ideas? Status Hierarchy and Indirect Influence - Carlson, Jenna; Lieburn, Sarah (My University, 2012)
In small-group settings, lower-status individuals are typically ignored, while higher-status individuals are attended to. As a result, the contributions of higher-status individuals have a direct impact on group decision making. Conversely, the contributions of lower-status individuals have little direct impact on decision making. When lower-status members do influence the group, they tend to have indirect influence that is not credited to them (Goodman, Alexander, Chizhik, Chizhik, & Eidelman, 2010). The purpose of this project was to determine how it feels to have an idea reflected in a groups' final decision in the absence of receiving credit for the idea.
Color poster with text and graphs.
Keywords: Competition (Psychology); Reward (Psychology); Social status; Marginality, Social; Dominance (Psychology); Posters